Performance Evaluation of Web Applications Using JMeter Load Testing for Server Capacity and Response Efficiency - Annisa, Aulia; Ardiana, Mirza; Rahayu, Putri Nur; Brian, Thomas; Jami’in, Mohammad Abu (Politeknik Negeri Batam, 2026)
The reliability of web-based conference systems is crucial for ensuring smooth services during periods of high activity. This research evaluates the performance of the ICOMTA PPNS journal website by conducting load testing using Apache JMeter with scenarios ranging from 50 to 5000 virtual users, each executed for one hour. The evaluation focuses on response time, error rate, throughput, and bandwidth usage. The results indicate that the website performs reliably with up to 200 concurrent users, demonstrating stable response times and no recorded errors. However, once the load surpasses 300 users, response times increase sharply exceeding 60 seconds and errors begin to appear, suggesting that the server has reached its performance limit. Under the heaviest load of 5000 users, throughput continues to rise, but overall service quality declines significantly. These findings highlight the need for server enhancements or migration to cloud-based infrastructure to ensure stable performance during peak usage.